An Analysis of Psychomotor Assessment Levels Based on Anderson and Krathwohl's Taxonomy in Integrated Thematic Books - Sajidan Sajidan; Fadhil Purnama Adi; Roy Ardiansyah; Idam Ragil Widianto Atmojo; Dwi Yuniasih Saputri; Gilang Mahendrati (AL-ISHLAH: Jurnal Pendidikan, 2022)
This study aims to analyze the psychomotor assessment levels based on Anderson and Krathwohl's taxonomy in the integrated thematic book for grade VI, theme 5, entrepreneurship. Methods: This content analysis research used a descriptive qualitative approach. The form of research data was a distribution of psychomotor assessments, categorized according to Anderson and Krathwohl’s taxonomy. The instrument validity used was the Gregory formula. Data validity employed was increased persistence and source triangulation. Sources were obtained from the teacher's book and coursebook. Data collection techniques utilized were document studies. The data analysis technique in this study applied an interactive analysis model from Miles and Huberman. Findings: The results showed that the distribution of psychomotor assessment levels at the imitation level (P1) was 23.33%, the manipulation level (P2) was 6.67%, the precision level (P3) was 36.67%, the articulation level (P4) was 30%, and the naturalization level (P5) was 3.33%. Conclusion: Therefore, it can be concluded that the precision level of psychomotor assessment is the most common because it follows the motor development of elementary school students who are expected to do things independently.